An algebra problem by Russell Garay

Algebra Level 2

simplify 72 + 72 + 72 + \sqrt{ 72 + \sqrt{ 72 + \sqrt{ 72 + \ldots } } }

9 12 6 8

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Rahul Pai
Nov 11, 2014

Lets take 72 + 72 + 72 + 72 + . . . . . . . . . . = x \sqrt { 72+\sqrt { 72+\sqrt { 72+\sqrt { 72+.......... } } } } = x

Then, x = 72 + x x = \sqrt {72+x}

So, x 2 = 72 + x x^2 = 72 + x

Then, x 2 x 72 = 0 x^2-x-72 = 0

Solving it, we get x = 9 x = 9 or x = 8 x = -8 .

In the options, since -8 is not given, 9 is the answer.

if -8 is in option then also we can't opt it. Because given(x) can never be -ve that's why we have to reject it, not because it is not in option :-)

Parveen Soni - 6 years, 7 months ago

can we do like this? x^2 - x - 72 =0 then ;x(x-1)=72 so the answer for x=72 or x=73

Efigenio Jay Baluyot - 6 years, 6 months ago

Log in to reply

No that's wrong.

Rohan Shah - 6 years, 6 months ago

You can only solve the equation that way when it equals 0, like if x(x-1)=0 instead of equaling 72. You have to factor it, which becomes (x+8)(x-9)=0, and then you can split it up and solve (x+8)=0, (x-9)=0, and thats how you get your answer. If you plugged the numbers you got for x back into the equation, you would get 72(72-1)=72, which doesn't work. I hope that made sense.

alex clifford - 6 years, 6 months ago

the two solutions won't be x=72 & x=73, rather they would be x=72/(x-1) and x=(72/x)+1.. your method is valid but only when the right side of the equation is 0 b'cuz the other term simply vanishes when it is made to divide 0.

Somesh Singh - 6 years, 6 months ago

If & only if ,their is zero on the place of 72 & then answer came out is 0 or 1

Gaurav Chamm - 6 years, 6 months ago

my procedure was derived while i was answering it mentally so pardon the less mathematical more logical approach haha i first assumed what would be the square of 72. being the closest perfect square is 81 and 64. one would assume that the value of the square of 72 is a value that is 9>x>8 or 8<x<9, since the equation state that we add the square of 72 to 72 before squaring it and since its infinite it is logical that the value that you will add to 72 before squaring it is a value near to 9 because of constantly adding terms. therefore 72 + 9 = 81, squaring 81, i got 9

Anna Anant
Nov 18, 2014

Let's say x = sqrt(72 + sqrt(72 + sqrt (72 + sqrt (72... So, x^2 = 72 + sqrt(72 + sqrt(72 + sqrt(72... Thus, x^2 - 72 = sqrt(72 + sqrt(72 + sqrt(72.. But we know that the long ass expression on the RHS is actually x. So we then have x^2 - 72 = x. We then have a quadraric equation x^2 - x -72 = 0. Since 72 is equal to 8 9, -72 can be equal to 8 times -9 or vice versa. We have -x in the eq, not +x. So choose -9 and 8. We can now rewrite the quadratic equation as (x - 9) (x + 8) = 0. Thus x = 9 or -8. We know that x must be +9 because a positive square root only has a positive answer.

Renah Bernat
Nov 18, 2014

Let's say x = sqrt(72 + sqrt(72 + sqrt (72 + sqrt (72... So, x^2 = 72 + sqrt(72 + sqrt(72 + sqrt(72... Thus, x^2 - 72 = sqrt(72 + sqrt(72 + sqrt(72.. But we know that the long ass expression on the RHS is actually x. So we then have x^2 - 72 = x. We then have a quadraric equation x^2 - x -72 = 0. Since 72 is equal to 8 9, -72 can be equal to 8 times -9 or vice versa. We have -x in the eq, not +x. So choose -9 and 8. We can now rewrite the quadratic equation as (x - 9) (x + 8) = 0. Thus x = 9 or -8. We know that x must be +9 because a positive square root only has a positive answer.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...